2013
DOI: 10.1002/psc.2534
|View full text |Cite
|
Sign up to set email alerts
|

A study of the anti‐plasmodium activity of angiotensin II analogs

Abstract: Controlling the dissemination of malaria requires the development of new drugs against its etiological agent, a protozoan of the Plasmodium genus. Angiotensin II and its analog peptides exhibit activity against the development of immature and mature sporozoites of Plasmodium gallinaceum. In this study, we report the synthesis and characterization of angiotensin II linear and cyclic analogs with anti-plasmodium activity. The peptides were synthesized by a conventional solid-phase method on Merrifield's resin us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 50 publications
4
33
0
Order By: Relevance
“…Conformational analysis of retro ‐AII indicated a randomly coiled conformation in all means evaluated. This might have led to reduced peptide–membrane interactions, in agreement with earlier studies that suggested that randomly coiled peptides show less effectiveness in the Plasmodium membrane disruption . The VC5 and all‐D ‐VC5 restricted analogs adopted predominantly a β‐turn conformation on all the means studied, and their antiplasmodial activity was consistently high.…”
Section: Resultssupporting
confidence: 88%
“…Conformational analysis of retro ‐AII indicated a randomly coiled conformation in all means evaluated. This might have led to reduced peptide–membrane interactions, in agreement with earlier studies that suggested that randomly coiled peptides show less effectiveness in the Plasmodium membrane disruption . The VC5 and all‐D ‐VC5 restricted analogs adopted predominantly a β‐turn conformation on all the means studied, and their antiplasmodial activity was consistently high.…”
Section: Resultssupporting
confidence: 88%
“…The substitution in a C-terminal extremity decreased peptide-parasite interaction (peptide 9 and peptide 10-70% and 73%, respectively). This behavior was observed by Chamlian, et al [7]. The antiplasmodial activity decreased in comparison to VIPF (analog 6), analog 7 and 8 had activity ≥ 75%.…”
Section: Resultssupporting
confidence: 69%
“…Based on the antiplasmodial activity reported by Maciel and Chamlian , we synthesized five AII‐restricted analogs that contained disulfide bridge cyclizations by inserting two Cys residues in the native sequence of the hormone.…”
Section: Resultsmentioning
confidence: 99%